The Influence Of Digital Transformation Culture On Collection Unit Performance Through Digital Technology (Case Study : Non-Bank Financial Institutions) - Cahyo Dananto, Dinar; Djunita Pasaribu, Rina (Publisher Cv. Inara, 2025)
This study analyzes the influence of digital transformation culture on organizational performance in the non-bank financial industry, focusing on the collection division as the executor of the collection process. Digitalization demands changes in organizational culture in order to optimize the value of digital technology in supporting business operations. This study aims to analyze the influence of digital transformation culture on the performance of collection organizations, test the influence of digital transformation culture on increasing the value of digital technology, evaluate the influence of digital technology value on collection organization performance, and test the mediating role of digital technology value in the relationship between digital transformation culture and organizational performance. A quantitative approach with a causal method is used in this study, with data collected through a survey of non-bank financial institution employees and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) software. The results of the study indicate that digital transformation culture has a positive effect on collection organization performance and digital technology value. In addition, increasing the value of digital technology also contributes to improving organizational performance, and plays a significant role in mediating the influence of digital transformation culture on organizational performance. Academically, this study enriches the literature on digitalization in operational management, while practically, the results of the study can be a reference for non-bank financial institutions in adopting a digital culture to improve operational effectiveness and organizational performance.